3D Printed Substrates for the Design of Compact RF Systems - Ghazalil, MIM; Mondal, S; Karuppuswami, S; Chahal, P (IEEE, 2024)
In this paper, Additive Manufacturing (AM) using 3D printing has been shown as a potential candidate for realizing customized compact solutions for RF packaging applications. Cost effective 3D printing based packaging solutions with customized substrates and air gaps allow easier integration of multiple RF components with lower substrate losses. Using a damascene-like conductor patterning process and a LEGO-like assembly process, an amplifier coupled to an air-substrate based patch antenna is demonstrated in a single integrated package.The antenna overlays the amplifier circuit leading to a compact design. The proposed customization of substrates and 3D printing strategies can be extended to multiple-system level stacking for SOP/SIP packaging customized for applications such as 5G.